Luminescence properties of Ca1-xSrxTiO3:Pr3+ - Park, C.-H.; Jeon, C.-I.; Yu, B.-Y.; Choi, H.; Bae, H.-S.; Kim, C.-H.; Pyun, C.-H. (Society for Information Display, 1998)
The phosphor CaTiO3:Pr3+ is highly regarded as a low-voltage red phosphor because of its good color quality and intrinsic conductivity. Under 330-nm excitation it shows red emission, which corresponds to the transition from 1D2 to 3H4. This transition is a forbidden f-f electric dipole transition, but its fluorescence intensity is quite large in CaTiO3:Pr3+ and decreases in Ca1-xSrxTiO3:Pr3+ as x increases. In this study, luminescence properties of CaTiO3:Pr3+ have been investigated in terms of crystal structure, using the Eu3+ ion as a probe. The Pr3+ ion site in the CaTiO3:Pr3+ has no centrosymmetry, and the partial allowance of the 1D2 → 3H4 transition by the odd crystal-field terms due to the loss of centrosymmetry gives quite strong emission. With the increase of the Sr ion substitution in Ca1-xSrxTiO3:Pr3+ prepared by heating at 1150°C, the fraction of the Pr3+ ions at inversion centers increases and the emission intensity decreases as the result.
Keywords: Calcium compounds; Crystal structure; Fluorescence; Photoluminescence; Calcium strontium titanate; Phosphors